Intellectual property, traditional knowledge and genetic resources / Michael Blakeney - Blakeney, Michael (Faculty of Administratron and Law, 2004)
Article 19 of the November 2001 Doha Declaration instructed the Council for TRIPS (Agreement on Trade-Related Aspects of Intellectual Property Rights 1994), in pursuing its work programme concerning both its review of Article 27.3(b) and its general review of the implementation of the TRIPS Agreement under Article 71.1, "to examine, inter alia, the relationship between the TRIPS Agreement and the Convention on Biological Diversity, the protection of traditional knowledge and folklore, and other relevant new developments raised by Members pursuant to Article 71.1".